Evaluation of lipid disorders and hyperglycemia in an open population aged 30-69 years: results of a multicenter study - M. N. Mamedov; L. T. Sushkova; R. V. Isakov; V. A. Kutsenko; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Aim. To identify lipid metabolism disorders and hyperglycemia in the open population aged 30-69 in 5 cities of the Vladimir region, taking into account sex characteristics.Material and methods. The study included 1350 people (men and women aged 30-69 years), while 1174 people completed the study; the response rate was 87%. There were 424 (36,1%) men and 750 (63,9%) women among those completed the study. All participants were interviewed according to a standard questionnaire, including questions on socio-demographic status, behavioral and biological risk factors for cardiovascular diseases, as well as the presence of somatic diseases and their treatment. The blood concentrations of total cholesterol (TC), triglycerides, high-density lipoprotein (HDL) cholesterol and glucose were determined.Results. The average indicators of TC in the adult population were 5,28±0,75 mmol/l, for men and women its level was comparable. Sex differences were revealed in the average blood level of HDL-C. In the male population, its level was 1±0,11 mmol/l, and among women it was 1,14±0,14 mmol/l (p<0,001). The blood concentration of triglycerides was significantly higher compared to women — 1,8 [1,5; 2,1] mmol/l in men vs 1,7 [1,3; 2,0] mmol/l in women (p<0,035). In the examined adult population, 56,7% had an elevated TC level, while the prevalence of hypercholesterolemia among men and women was comparable — 57,8 and 55,7%, respectively. Hyperglycemia was found in 22% of all examined, while among men it was detected in every fourth, and among women in every fifth. Sex differences were significant (p=0,045). The prevalence of prediabetes among men is significantly higher compared to women — 17,2 and 11,9% (p=0,013), while the prevalence of diabetes in men and women was comparable — 7,3 and 7,6%, respectively.Conclusion. Every second participant among men and women of the Vladimir region population has hypercholesterolemia, while fasting hyperglycemia is detected in every fourth man and fifth woman. Among men, the incidence of prediabetes is 2,5 times, and among women 1,5 times higher than the prevalence of diabetes. Thus, development of preventive interventions in a particular region of the Central Federal District should take into account the high prevalence of hypercholesterolemia and hyperglycemia, including early disorders of carbohydrate metabolism.